2014
DOI: 10.1590/2176-9451.19.6.113-122.bbo
|View full text |Cite
|
Sign up to set email alerts
|

Class II malocclusion nonextraction treatment with growth control

Abstract: The present study reports a case of Angle Class II malocclusion treatment of a male growing patient with 10-mm overjet, excessive overbite and transverse maxillary deficiency. The case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO), with DI equal to or greater than 10, as a requirement for the title of certified by the BBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Indeed, this outcome may have been circumvented by opting for a non-extraction treatment option with conventional methods. [35][36][37] However, for this case, the extent of crowding was considerable and required space for the distalization of canines to achieve a Class I canine relationship. Few studies have reported the successful treatment of complex cases with clear aligners, and robust evidence through randomized controlled trials is lacking.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, this outcome may have been circumvented by opting for a non-extraction treatment option with conventional methods. [35][36][37] However, for this case, the extent of crowding was considerable and required space for the distalization of canines to achieve a Class I canine relationship. Few studies have reported the successful treatment of complex cases with clear aligners, and robust evidence through randomized controlled trials is lacking.…”
Section: Discussionmentioning
confidence: 90%
“…To evaluate the permanent and mixed dentition, the Discrepancy Index used by the American Board of Orthodontics ( Figure 1 ) [ 23 ] was used to determine the difficulty of orthodontic treatment in a sample of clinical photographs and radiographs of children with OI as well as in a sample of healthy controls. Four degrees of difficulty were defined according to the score (low: 0–7 points; moderate-low: 8–15 points; moderate-high: 16–25, and high: >26 points).…”
Section: Methodsmentioning
confidence: 99%
“… ABO Discrepancy Index [ 23 ]. American Board of Orthodontics (ABO); Analysis of the intermaxillary relationship (ANB); Sella Nasion and mandibular plane (SN-MP).…”
Section: Figurementioning
confidence: 99%